DICTONS ROMANS AVEC LES DOUZE MOIS : LA CARACTÉRISATION PARÉMIQUE ET MENSUELLE DE L’ANNÉE - BASTARDAS RUFAT, Maria-Reina; FONTANA I TOUS, Joan; GARGALLO GIL, José Enrique (Studia Universitatis Babeș-Bolyai Philologia, 2020)
Romance Proverbs with the Twelve Months: the Paremical and Monthly Characterization of the Year. There are various types of weather and calendar proverbs in the romance languages. Not only concerning their motivation, but also concerning their length. Among the proverbs referring to the months, some are very short, just two or three words, the so-called "minimal proverbs", while others are quite long, and curiously defy any kind of mnemonics. Our corpus will be made up of the latter type: thirteen proverbs mentioning all the twelve months of the year, which represent five different Romance varieties; from west to east: Portuguese (1 proverb), Spanish (2), Catalan (5), Italian (4) and the Laziale Italian variant (1). We classify these formulae, which lie on the thresholds of what strictly might be considered proverbs, in two groups: proverbs without meteorological implication and meteorological proverbs. On the other hand, we classify the examples of the second group in four sections according to the characteristics that are attributed to one or several months: proverbs with a characteristic for several months, proverbs with a characteristic for each pair of months, proverbs with a characteristic for some of the months, and sayings attributing a different feature for each month. This corpus offers a glimpse to the way Romance peoples view the months and it reveals affinities in the form of paremic types (or "paremiotypes"), which tell us about the popular culture shared by the peoples that are heirs of Rome. REZUMAT. Proverbe romanice cu cele douăsprezece luni: caracterizarea paremiologică şi lunară a anului. În ţările romanice, există mai multe tipuri de proverbe meteorologice şi calendaristice. Nu numai în legătură cu motivaţia lor, dar, de asemenea, cu lungimea lor. Dintre proverbele care se referă la luni, câteva sunt foarte scurte: de pildă, aşa-zisele „proverbe minime” au doar două cuvinte; mai sunt însă alte proverbe atât de lungi, încât, curios lucru, îngreunează orice fel de mnemotehnică. Tocmai din acestea din urmă fac parte proverbele corpusului nostru; este vorba, anume, despre treisprezece înşirări paremiologice referitoare la cele douăsprezece luni ale anului, care reprezintă cinci varietăţi romanice diferite; de la vest la est, portugheza (un proverb), spaniola (2), catalana (5), italiana (4) şi varianta italiană din Lazio (1). Aceste formule, care se află la limita a ceea ce am putea considera strict proverbe, se clasifică, întâi, în două grupe: proverbe fără nicio implicare meteorologică şi proverbe meteorologice. Pe de altă parte, grupăm exemplele din al doilea grup în patru capitole în acord cu caracteristicile care se atribuie la una sau la mai multe luni: proverbe cu o caracteristică pentru diferite luni, proverbe cu o caracteristică pentru câte două luni, proverbe cu o caracteristică pentru unele dintre luni şi proverbe cu o caracteristică pentru fiecare lună. Ansamblul oferă o privire romanică asupra cursului anului, care pune în evidenţă afinităţi sub forma unor „paremiotipuri” ale căror formule ne povestesc despre cultura tradiţională împărtăşită de acele popoare care sunt moştenitoarele Romei. Cuvinte-cheie: proverbe, lună, an, meteorologie, limbi romanice.